2022
DOI: 10.1021/acs.jafc.1c06420
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Stereoselectivity Study of Fenobucarb: Environmental Behaviors in Greenhouse Vegetables, Fruits, Earthworms, and Soils and Its Cytotoxicity

Abstract: Fenobucarb (2-sec-butylphenyl methylcarbamate, BPMC) is a potent carbamate pesticide with high insecticidal activity. In this study, the enantioselective accumulation of BPMC in earthworms (Eisenia foetida) and dissipation in cabbage, Chinese cabbage, strawberry, and soils were investigated. The samples were prepared using the QuEChERS method and analyzed using fast and sensitive chiral high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) analysis. The stereoselective accumulation of BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…sativum Linn plants . The different half-lives of fenobucarb enantiomers were found in cabbage and Chinese cabbage . Besides, the enantioselective dissipations of penflufen enantiomers were also found in spinach and Chinese cabbage after spraying (22% of the penflufen suspension) .…”
Section: Resultsmentioning
confidence: 94%
“…sativum Linn plants . The different half-lives of fenobucarb enantiomers were found in cabbage and Chinese cabbage . Besides, the enantioselective dissipations of penflufen enantiomers were also found in spinach and Chinese cabbage after spraying (22% of the penflufen suspension) .…”
Section: Resultsmentioning
confidence: 94%
“…The opposite stereoselectivity of pydiflumetofen was found in grape and soil . Plant enzymes and soil microbial populations play a key role in the stereoselective dissipation of chiral pesticides. Biological processes such as oxidation and reduction of enzymes and microbial action play an important role in stereoselective dissipation of compounds. Han et al found that bacterial genera Burkholderia , Paraburkholderia , Hyphomicrobium , and Methylobacterium might play pivotal roles in the preferential dissipation of R -mandipropamid in repeatedly treated soils .…”
Section: Resultsmentioning
confidence: 99%
“…Due to solubility of these insecticides in water, fenobucarb 420 mg/L at 20 o C and propoxur 1860 mg/ L at 30 o C (Pham et al 2021;Tabibi and Jafari 2006), they have the potential to enter the surface water through surface run off and also leach down into groundwater. This leads to their residues in different environmental segments and accumulation in humans and other non-target species, which causes potential hazard to human health and environment (Zheng 2017;Ma et al 2022;Lawrence et al 2009;Tada et al 2009). The toxicity of these insecticides makes the monitoring of fenobucarb and propoxur essential for their environmental risk assessment, to decrease potential hazard to the environment.…”
Section: Introductionmentioning
confidence: 99%